Proposal of a new parameter for evaluating muscle mass in footballers through bioimpedance analysis - Levi Micheli, M.; Cannataro, R.; Gulisano, M.; Mascherini, G. (Biology, 2022)
Simple Summary Body composition assessment in athletes is closely related to sports performance. In sports where alternating aerobic and anaerobic metabolism is required, muscle mass can affect the achievable result. Therefore, the assessment of muscle mass is a field of interest in the sports sciences. Bioimpedance analysis is a method for assessing body composition. Currently, bioimpedance evaluates muscle mass through predictive equations that could provide estimation errors. These errors could be reduced by an evaluation of the raw bioelectrical parameters. Therefore, in this study, we propose a new parameter for assessing the muscle mass in athletes.